2022
DOI: 10.3390/life12111719
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lentil (Lens Culinaris (Medik.)) Genotypes Suitable for High-Temperature Conditions Based on Stress Tolerance Indices and Principal Component Analysis

Abstract: Legumes, including lentil, are a valuable source of carbohydrates, fiber, protein and vitamins and minerals. Their nutritional characteristics have been associated with a reduction in the incidence of various cancers, HDL cholesterol, type 2 diabetes and heart disease. Among these quality parameters, lectins have been associated with reducing certain forms of cancer, activating innate defense mechanisms and managing obesity. Protease inhibitors such as trypsin and chymotrypsin inhibitors have been demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Further studies will be required on the best performing accessions identified in this first screening in the test area, considering the interaction between genotype and environment. Other authors have already provided findings under high-temperature conditions using stress tolerance indices [31] or focusing on production stability and quality traits specifically in Southern Italy [77]. In this research context, it will therefore be appropriate to further evaluate abiotic stress phenomena and their influence in order to identify the most suitable genotypes in this particular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will be required on the best performing accessions identified in this first screening in the test area, considering the interaction between genotype and environment. Other authors have already provided findings under high-temperature conditions using stress tolerance indices [31] or focusing on production stability and quality traits specifically in Southern Italy [77]. In this research context, it will therefore be appropriate to further evaluate abiotic stress phenomena and their influence in order to identify the most suitable genotypes in this particular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Several traits related to grain yield and protein content have been indicated as relevant aspects for the selection of genotypes for breeding improvement [28]. The generation of hybrids through crosses using commercial varieties and crosses between accessions could be an alternative practice to conventional breeding methods for boosting seed yields [29] as well as for increasing resistance to abiotic and biotic stress [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The in-depth study of plant-microbe interaction has become even more pertinent because abiotic stresses have raised interest in developing microbe-based stress mitigation strategies [25][26][27]. The abiotic stresses, especially drought stress (DS) and high temperature stress (HS), have caused serious losses to the productivity of farming systems [28][29][30][31][32], which necessitates research efforts in order to devise plant-microbe-interaction-based strategies. Figure 1 elucidates different types of abiotic stresses (e.g., heat, drought, salinity, water logging, heavy metals toxicity), especially drought-induced alterations in crop plants (e.g., plasma membrane deterioration, impaired photosynthesis, transpiration losses) and in microbes (Psychrophilic microbes population decreases under elevated temperatures, in contrast to Psychrotrophic microbes).…”
Section: Introductionmentioning
confidence: 99%